INSIGHTS ON THE NORTH CHINA LEOPARD (PANTHERA PARDUS JAPONENSIS GRAY, 1862): CHALLENGES IN DISTRIBUTION, POPULATION STATUS, THREATS, AND IMPLICATIONS FOR CONSERVATION - K. Vitekere; K. Tulizo; M. Zaman; H. Karanja; Y. Hua 4; G. Jiang1 (Journal of Animal and Plant Sciences, 2020)
China has four sub-species of leopard throughout the country. One of them is the North China leopard (Panthera pardus japonensis, Gray, 1862) which experiences a wide range of threats. It remains at the centre of interest for recent research and new management policies within its natural habitat. Due to limited studies for a long time, its current distribution, and population size remain vague without accurate information. Using existing literature, we synthesized information on this endemic and endangered subspecies. We used research engines such as Google scholar, Baidu and China National Knowledge Internet (CNKI) to find any available literature about the sub-species. By reviewing 39 published documents, nine national and international web news, and asking questions to some specialists in leopard and wildlife managers; we have concluded that the species' current distribution has drastically changed, only 2 % of its historical distribution remains occupied by around 174-348 individuals. Extant patches are in continual danger as the Proximity Index previously found was small. Habitat fragmentation, retaliation, and decline in prey species are the main threats. However, there is hope for its survival, since the mega project launched in 2015 "Bring Leopards Home" and new management policies are being undertaken in protected areas that will annihilate or reduce threats. In addition, many researchers or governmental organisations are currently carrying out studies on this sub-species. These studies will fill information gaps on the North China leopard based on scientific evidence.
Keywords: Conservation and management; distribution; habitat ranges; North China leopard; patch; sub-species; threats